Financial reform after the crisis: An early assessment - Nicolas Véron (Bruegel, 2012)
This paper takes stock of global efforts towards financial reform since the start of the financial crisis in 2007-08, and provides a synthetic (if simplified) picture of their status as of January 2012. Underlying dynamics are described and analysed both at the global level (particularly G-20, International Monetary Fund and the Financial Stability Board) and in individual jurisdictions, together with the impact the crisis has had on them. The possible next steps of financial reform are then reviewed along several dimensions including ongoing crisis management in Europe, the new emphasis on macroprudential approaches, the challenges posed by globally integrated financial firms, the implementation of harmonised global standards and the links between financial systems and growth.
Keywords: 330